ANALYSIS OF ANTIOXIDANT ACTIVITY ETHANOL EXTRACT TELANG FLOWER LEAVES (Clitoria ternatea L.) USING THE DPPH METODH - Herlina; Elly Mulyani; Devi Novia; Tri Yanuarto (PUCUK : Jurnal Ilmu Tanaman, 2024)
Butterfly pea flower is a plant that has many pharmacological benefits, including antioxidant, antibacterial, anti-inflammatory and analgesic, antidiabetic, anticancer, antihistamine and immunomodulator. The results of phytochemical screening of telang flower leaves are contain secondary metabolites is flavonoids, alkaloids, saponins, quinones, polyphenolates, triterpenoids and steroids. The presence of flavonoid compounds in butterfly pea flowers allows for antioxidant activity. The aim of this research to determine the antioxidant activity of ethanol extract butterfly pea flower leaves (Clitoria ternate L.) using DPPH method. Simplicia butterfly pea flower leaves (Clitoria ternate L.) were extracted using maceration method with 96% ethanol solvent. The extract obtained was antioxidant test using spectrophotometry UV-VIS with a wavelength of 517 nm. The data obtained for the antioxidant activity value and expressed as IC50 (inhibition concentration) value which shows the concentration of antioxidant compound that inhibit 50% of DPPH radical activity. The results of the research show that ethanol extract of butterfly pea flowers leaves (Clitoria ternate L.) has the ability to act as a very strong antioxidant with an IC50 value of 6,056 ppm.